Determining the adsorption energies of small molecules with the intrinsic properties of adsorbates and substrates - Wang Gao (Nature Portfolio, 2020)
Adsorption of molecules at surfaces is at the basis of many processes in chemistry. Here the authors propose an approach to determine the adsorption energies of different chemical species on a variety of solid surfaces based on fundamental and accessible properties of adsorbate and surface atoms.